Historiografi Kajian Living Hadis di Indonesia - Ihsan, Muhammad Faqih; Ashshiddieqi, Muhammad Naufal (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2024)
The study of living hadith is a widely used approach to read hadith-based religious practices in society. However, in the last decade (2015–2023), findings show that research on living hadith tends to be stagnant because it focuses too much on the traditional aspects of practice, while the more complex aspects of transmission and transformation are still not paid attention. This shows that there are gaps and potential for further development in the study of living hadith, especially through a more diverse and in-depth approach. This research aims to map the trends, developments, and peculiarities of living hadith studies that have developed in Indonesia over the past ten years. Using the Systematic Literature Review (SLR) method, the author searched 21 academic literature with the keyword